Biosurfactant producing multifarious Streptomyces puniceus RHPR9 of Coscinium fenestratum rhizosphere promotes plant growth in chilli. - Polapally Ravinder; M Manasa; D Roopa; Najat A Bukhari; Ashraf Atef Hatamleh; Mohamed Yahya Khan; Reddy M S; Bee Hameeda; Hesham Ali El Enshasy; Siti Zulaiha Hanapi; R Z Sayyed (PLoS ONE, 2022)
The present study involves isolation of Streptomyces spp. from rhizosphere of Coscinium fenestratum Gaertn, an endangered medicinal plant from Western Ghats of Karnataka, India. Four potential isolates were identified by 16S rRNA sequencing as Streptomyces sp. RHPR3, Streptomyces puniceus RHPR9, Streptomyces sp. RHPR14 and Streptomyces mediolani RHPR25. An enrichment culture method was used for the isolation of Streptomyces spp. for biosurfactant activity. Among four potential Streptomyces spp., S. puniceus RHPR9 showed highest Emulsification index (EI) (78±0.2%) and Emulsification assay (EA) (223±0.2 EU mL-1). Thin layer chromatography, Fourier transform infrared spectroscopy (FTIR) and mass spectrometric analysis revealed that as glycolipid. Further confirmed by presence of fatty acids like hexanoic acid methyl ester, decanoic acid by Gas chromatography mass spectroscopy (GC-MS) analysis. S. puniceus RHPR9 showed a significant IAA production (41μg mL-1), solubilized P (749.1 μg mL-1), growth promotion of chilli (Capsicum annuum L.) was evaluated using paper towel method and greenhouse conditions. S. puniceus RHPR9 showed a significant increase in seed vigor index (2047) and increase in plant biomass (65%) when compared to uninoculated control. To our knowledge, this is the first report on epiphytic S. puniceus RHPR9 isolated from an endangered medicinal plant C. fenestratum Gaertn, for biosurfactant production and plant growth promotion activities.